1993
DOI: 10.1289/ehp.939989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA adducts from exposure to complex mixtures in various human tissues and experimental systems

Abstract: DNA adducts derived from complex mixtures of polycyclic aromatic compounds emitted from tobacco smoke are compared to industrial pollution sources (e.g., coke ovens and aluminum smelters), smoky coal burning, and urban air pollution. Exposures to coke oven emissions and smoky coal, both potent rodent skin tumor initiators and lung carcinogens in humans, result in high levels of DNA adducts compared to tobacco smoke in the in vitro calf thymus DNA model system, in cultured lymphocytes, and in the mouse skin ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…It is also noteworthy that the persistency of the dose-response relationship in mouth floor cells (the target cell type for oral cancer) even after exclusion of the nonsmokers from the analysis. This is in good conformity with other studies demonstrating such dose-response relationships only in cells from the target sites, e.g., lung, larynx, but not from the surrogate ones, e.g., blood cells [Lewtas et al, 1993;Randerath and Randerath, 1993;Philips, 1996]. Regarding the cumulative dose of exposure, however, lack of relation between adduct levels in either mouth floor cells or buccal mucosa cells and smoking history index (pack years) was not unexpected because oral cells are exfoliated cells with a short life span ranging from a few days to a week [Stich et al, 1983].…”
Section: Discussionsupporting
confidence: 92%
“…It is also noteworthy that the persistency of the dose-response relationship in mouth floor cells (the target cell type for oral cancer) even after exclusion of the nonsmokers from the analysis. This is in good conformity with other studies demonstrating such dose-response relationships only in cells from the target sites, e.g., lung, larynx, but not from the surrogate ones, e.g., blood cells [Lewtas et al, 1993;Randerath and Randerath, 1993;Philips, 1996]. Regarding the cumulative dose of exposure, however, lack of relation between adduct levels in either mouth floor cells or buccal mucosa cells and smoking history index (pack years) was not unexpected because oral cells are exfoliated cells with a short life span ranging from a few days to a week [Stich et al, 1983].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore linear correlations could be anticipated in this case. Heart was included in the present study because, while examining several autopsy tissues of humans previously exposed to tobacco smoke, Lewtas et al (1993) has shown that the highest DNA-adduct level was detected in human heart followed by that in lung. The same authors have raised the importance of studying both lung and heart target cells for improvement of the sensitivity of DNA-adduct dosimetry on target cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Some DNA adducts derived from complex mixtures of PAHs occurring in the environment (e.g., diesel emissions and tobacco smoke) were found to be sensitive to P1 dephosphorylation [Lewtas et al, 1993;Gallagher et al, 1994]. However, it should be remembered that many adducts, such as (ϩ)-N 2 -(7R.8S.9R-trihydroxy-7,8,9,10-tetrahydrobenzo[a]pyrene-10s-yl)2Ј-deoxyguanosine (N 2 -BPDEdGp) show similar recoveries with the two techniques and that adduct profiles for many specific carcinogens (e.g., benzo[a]pyrene, dimethylbenz[a]anthracene) and in certain human tissues (e.g., bronchial tissue) have been found to be predominantly similar [Gupta and Early, 1988;Gallagher et al, 1989;Phillips et al, 1990;Ashby et al, 1993].…”
Section: Discussionmentioning
confidence: 99%